DRESS SYNDROME AS SERIOUS SKIN HYPERSENSITIVITY REACTIONS ASSOCIATED WITH OLANZAPINE: CASE REPORT - Javed Ather Siddiqui; Shazia Farheen Qureshi; Amr Ahmed Hafez; Waseem M Marei (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Introduction – There are a variety of symptoms associated with this serious idiosyncratic adverse reaction, including fever, skin eruption, lymphadenopathy, eosinophilia, organ involvement, and hematologic abnormalities which clinical manifestations occur two weeks to two months after a triggering drug was administrated. Methods – Presented the case of a 50-year-old male who developed severe generalized erythroderma with exfoliative scaling skin erythema and maculopapular eruptions all over the body. This was associated with fever, eosinophilia, and leukocytosis after olanzapine ingestion. Results – This case called Dress syndrome, and the atypical antipsychotic olanzapine is one of the causes of this illness. This adverse effect is life-threatening, so early diagnosis reduces morbidity and mortality. Discuss – It is imperative that health care professionals and caregivers are aware of the symptoms of such life-threatening reactions during and after treatment. It is also necessary to understand the pathogenesis of diseases in order to develop personalized treatment plans. The medication history of patients with suspected DRESS must be checked. Conclusion – Dress syndrome is a serious and potentially devastating side effect of psychotropic medication. It is possible to experience adverse drug reactions after one dose or prolonged use of a drug or following a combination of two or more drugs. It is important for health care professionals and caregivers to be aware of the symptoms of such life -threatening reactions as part of the aftercare process during treatment. In order to develop personalized treatment plans, more research is necessary to elucidate its pathogenesis. It is imperative to check the medication history of patients with suspected DRESS. Usually, a patient who has previously taken a suspected drug will experience symptoms within two weeks of taking it.     Keywords: Olanzapine, psychosis, drug hypersensitivity syndrome, skin rash.